Zirconium Nanoparticles Based Vortex Assisted Ligandless Dispersive Solid Phase Extraction for Trace Determination of Lead in Domestic Wastewater using Flame Atomic Absorption Spectrophotometry - Ay, Esma; Tekin, Zeynep; ozdogan, Nizamettin; Bakirdere, Sezgin (SPRINGER, 2022)
In this paper, a sensitive and simple zirconium nanoparticles (Zr-NPs) based vortex assisted ligandless dispersive solid phase extraction (VA-LDSPE) method was developed for the preconcentration of lead from wastewater samples for the determination by slotted quartz tube-flame atomic absorption spectrometry (SQT-FAAS). Zr-NPs were synthesized using zirconium (IV) chloride salt as a starting material through a simple reduction process with sodium borohydride, and used as selective adsorbent for the extraction of lead ions from aqueous medium. Single variant experiments were carried out for all optimizations of sorption/desorption steps including pH of solution, amount of nanoparticles, mixing type/period and eluent type. An SQT with five round slots was placed onto the burner of FAAS to increase the interaction between lead atoms and light from radiation source to enhance the absorbance signals. Under the determined optimum conditions, analytical figures of merit were evaluated and the limit of detection and quantification (LOD/LOQ) values were calculated as 5.2 and 17.3 mu g L- 1, respectively. The developed method showed a linear calibration range between 25 and 250 mu g L- 1 with a good regression coefficient value (0.9995). Recovery studies were also performed with domestic wastewater samples spiked at three concentrations and percent recovery values obtained in the range of 97%-102% validated the developed method's applicability and accuracy.
Keywords: Lead; Zirconium nanoparticles; Flame atomic absorption spectrophotometry; Slotted quartz tube; Ligandless dispersive solid phase extraction; Wastewater samples; LIQUID-LIQUID MICROEXTRACTION; ONLINE PRECONCENTRATION; CADMIUM; SAMPLES; COPPER; ADSORPTION; COBALT(II); SEPARATION; NICKEL; IONS; Environmental Sciences & Ecology; Toxicology